Effect of liming on yield and quality of pepperment and Sachalin mint in fine sand soil of Northern Finland - Aflatuni, Abbas; Uusitalo, Jouko; Ek, Sari; Hohtola, Anja (Jokioinen : Agricultural Research Centre of Finland, 2003)
Selostus: Kalkituksen vaikutus piparmintun ja Sachalinin mintun satoon Pohjois-Suomessa